2017
DOI: 10.1016/j.energy.2017.03.104
|View full text |Cite
|
Sign up to set email alerts
|

Local resolved investigation of hydrogen crossover in polymer electrolyte fuel cell

Abstract: In this study, the effects of temperature, pressure and relative humidity (RH) on hydrogen crossover rate from anode to cathode of a PEMFC is investigated.Segmented cells are used to measure the local hydrogen crossover current density (j cross H2 ) distribution. The results present approximate linear increase of the hydrogen crossover rate with increasing temperature and hydrogen back pressure with rates of 0.038 mA cm -2 K -1 and 3.33 mA cm -2 bar -1 , respectively. Generally, slightly increased H 2 crossove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Moreover, they confirmed that hydrogen cross‐infiltration mainly occurred at the inlet and the outlet was negligible. Similar research was considered by Shan et al with segmented cells, and the result showed that relative humidity had a more complicated relationship to hydrogen crossover compared with the linear effects of temperature and pressure on hydrogen crossover. Giner‐Sanz et al developed a model based on commercial membranes, which described the effects of anode and cathode pressure on internal short circuit and hydrogen crossover.…”
Section: Introductionsupporting
confidence: 84%
“…Moreover, they confirmed that hydrogen cross‐infiltration mainly occurred at the inlet and the outlet was negligible. Similar research was considered by Shan et al with segmented cells, and the result showed that relative humidity had a more complicated relationship to hydrogen crossover compared with the linear effects of temperature and pressure on hydrogen crossover. Giner‐Sanz et al developed a model based on commercial membranes, which described the effects of anode and cathode pressure on internal short circuit and hydrogen crossover.…”
Section: Introductionsupporting
confidence: 84%
“…During fuel cell operation, only the same ions (protons or OH − -ions) are generated [ 52 , 53 , 54 ]. Nevertheless, even in this case, it is necessary to limit gas diffusion through the membrane as much as possible, which determines the so-called fuel crossover—the undesired passage of fuel, not accompanied by energy production [ 55 , 56 , 57 ]. The ratio of fluxes of desired and undesired components determines the value of selectivity, which is one of the most important membrane operating parameters [ 37 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of oxygen, the currents are negative over the entire active area (Figure 5B). The average current density is −3.6 mA cm −2 , which is a typical value for hydrogen crossover at this membrane thickness [36] . Since no oxygen is present, no ORR takes place and therefore no positive currents were measured in Figure 5B.…”
Section: Resultsmentioning
confidence: 86%
“…The average current density is À 3.6 mA cm À 2 , which is a typical value for hydrogen crossover at this membrane thickness. [36] Since no oxygen is present, no ORR takes place and therefore no positive currents were measured in Figure 5B. In contrast, at an oxygen content of 6.9 vol.…”
Section: Capacitance In the Presence Of Oxygenmentioning
confidence: 92%